Implementation of Technology-Based Learning (Utilization Of Technology In Smart Digital Class and Regular Class at MA Sunniyyah Selo) - Jamalullael, Jaiz; Rifiq, Ahmad; Yahya, Imam; Ridwan, Muhammad K.; Wangsanata, Susana Aditiya (Universitas Wahid Hasyim Semarang, 2024)
AbstractDigitalization of education is now unavoidable. The use of digital media in learning is one way that can be done in the process of digitizing education. The aim of this research is to explore the application of technology-based learning in smart digital classes and regular MA Sunniyah Selo classes. This research uses a qualitative method with a case study approach. The case study in this research is used to compare technology-based learning in the two different classes. Observations, documentation and interviews were carried out to collect data before analysis was carried out by sorting, grouping, coding, looking for appropriate themes for later interpretation. The research results show that differences in digital media access in the learning process are not a differentiating factor in learning outcomes between smart digital classes and regular classes. Even some of the advantages of learning in smart digital classes are weaknesses in regular classes. Likewise, the advantages of the regular class are the weaknesses of the smart digital class. This shows that the effectiveness of technology-based learning in smart digital classes and regular classes influences the strategies, methods and approaches in the learning process. So that this can be used as a reference in developing technology-based learning in two different classes at once.